A review on the role, cost and value of hydrogen energy systems for deep decarbonisation. (March 2019) - Parra, David; Valverde, Luis; Pino, F. Javier; Patel, Martin K.
Abstract: Hydrogen technologies can play an important role in decarbonising our energy system in a variety of ways across the energy value chain. It is therefore critical to identify the strategic roles as well as the conditions under which hydrogen energy systems become attractive for the energy transition. In this paper, the authors present a techno-economic review of hydrogen energy systems including power-to-power, power-to-gas, hydrogen refuelling and stationary fuel cells. We focus on their optimal operation as flexible assets and we identify three actions that can foster their uptake beyond technological progress. First, we recommend optimal electricity supply with dedicated control strategies considering that electricity dominates the levelised cost of hydrogen production via electrolysis. Secondly, hydrogen can enable the further integration of traditionally independent sectors, namely electricity, heat and transport while contributing to decarbonise all. This position can also be advantageous for investors who sell heat and fuels as energy efficient products. Lastly, we examine a whole range of revenues from different products and applications which can be combined (i.e. benefit stacking) to match capital and operational expenditures. We discuss these roles in depth and we conclude that policy makers together with technology developers should elaborate smart strategies to reduce cost by scaling production, stimulate standardisation (e.g., similar to the PV industry) as well as develop new market structures and regulatory frameworks which allow hydrogen technologies to deliver multiple low carbon applications and products. Highlights: The role of PtG, power-to-power, hydrogen refuelling and fuel cell are evaluated. The value of various products and services offered by hydrogen systems is given. Recommendations are given for minimising the levelised cost of electrolysis. We review electronics and control techniques for various hydrogen energy systems. Key strategies such as further system linkage and benefit stacking are discussed.